Assessment of Health Risk of Exposure to Chemical Pollutants Based on Program of Respiratory Protection at a Petrochemical Company in Mahshahr - Adel Sharifi; Anoosh sadat Amini nasab; Amin Delavar (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction: Chemicals are one of the most important sources of contaminants that over time cause severe problems for employees exposed to various chemicals in the refining process units . The purpose of this study was to determine the highest level of exposure to BTEX compounds and to assess the health risk caused by exposure to refinery personnel in a petrochemical company in Mahshahr City, Iran. Methods: The present descriptive-analytical study was conducted in a petrochemical company in Mahshahr City during 2016-2017.  In this study, we identified the causes of workplace harm by occupational groups. Air sampling and BTEX analysis were performed according to NIOSH method number 1501. To analyze the results, SPSS software was used. Finally, the risk assessment was done in accordance with the method number 84101042 of Oil Ministry. Results: The results of this study showed that benzene with a mean density of 0.58, 0.43, and 0.38 ppm in the work areas of site men, shift workers, and a supervisor had the highest density compared with ethyl benzene and toluene. Based on the results, 66.7%, 8.3%, and 12.5% of risk levels were low, high, and moderate/very high. respectively. Conclusion: According to the results, benzene has the highest health risk among the petrochemicals produced in petrochemicals. Due to the high level of exposure to benzene, it is recommended to take corrective and preventive measures to eliminate or reduce its exposure.